2013
DOI: 10.1371/journal.pone.0054329
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analyses of Small Theropod Dinosaur Teeth and Implications for Paleoecological Turnover through Time

Abstract: Isolated small theropod teeth are abundant in vertebrate microfossil assemblages, and are frequently used in studies of species diversity in ancient ecosystems. However, determining the taxonomic affinities of these teeth is problematic due to an absence of associated diagnostic skeletal material. Species such as Dromaeosaurus albertensis, Richardoestesia gilmorei, and Saurornitholestes langstoni are known from skeletal remains that have been recovered exclusively from the Dinosaur Park Formation (Campanian). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
188
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(200 citation statements)
references
References 40 publications
(50 reference statements)
11
188
0
1
Order By: Relevance
“…Zinke, 1998;Smith & Dodson, 2003;Larson & Currie, 2013); • Analysis of denticle shapes (square, rectangular or subquadrangular); • Shape of the basal cross section (leaf shape or oval shape); • Crown base width (CBW), roughly similar to the tooth basal width (BW) of some authors (e.g. Zinke, 1998;Smith & Dodson, 2003;Larson & Currie, 2013); • Extension of the area without denticles, if present (both in the apical and basal portions); • Presence or absence of enamel wrinkles; • Symmetry; • Size of the grooves present in denticles;…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinke, 1998;Smith & Dodson, 2003;Larson & Currie, 2013); • Analysis of denticle shapes (square, rectangular or subquadrangular); • Shape of the basal cross section (leaf shape or oval shape); • Crown base width (CBW), roughly similar to the tooth basal width (BW) of some authors (e.g. Zinke, 1998;Smith & Dodson, 2003;Larson & Currie, 2013); • Extension of the area without denticles, if present (both in the apical and basal portions); • Presence or absence of enamel wrinkles; • Symmetry; • Size of the grooves present in denticles;…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly the case for teeth, which compose a substantial portion of the fossil record of vertebrates (e.g. Rauhut & Werner, 1995;Zinke, 1998;Heckert, 2004;Larson & Currie, 2013;Sues & Averianov, 2013;Hendrickx et al, 2015). In areas where other osteological elements are rare or absent, the dental record may provide important information about the faunal composition of a locality.…”
Section: Introductionmentioning
confidence: 99%
“…Little skeletal material has been described, and skull material is particularly rare (Carpenter 1982;Fiorillo et al 2009;Makovicky and Norell 2004;Russell 1969;Zanno et al 2011), hindering assessments for taxonomic diversity in the group. Despite this, isolated troodontid teeth are relatively common through the Campanian and Maastrichtian of western North America (Cullen and Evans 2016;Larson et al 2016;Larson and Currie 2013). Historically, the genus Troodon has been reported to occur throughout the Campanian and Maastrichtian, and across most of western North America , based on referrals of isolated teeth and the few, and generally fragmentary, available fossils (Zanno et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In a subsequent morphometric study of isolated small theropod teeth from the latest Cretaceous of western North America, Larson and Currie (2013) also concluded that their diversity is underestimated, and that T. formosus sensu stricto is only definitively known from the Judith River and Dinosaur Park formations, implying teeth from other units may represent distinct taxa.…”
mentioning
confidence: 99%
See 1 more Smart Citation